2010
DOI: 10.1111/j.1744-7348.2010.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

On the efficiency of legume supernodulating mutants

Abstract: The supernodulating mutants of legumes lack the internal regulation of the number of symbiotic root nodules that harbour N2‐fixing nodule bacteria. On one hand, these mutants represent an efficient tool for dramatic increase in the degree of rhizobial symbiosis development. The trait of released nodulation is often associated with the desirable resistance of nodule initiation and functioning to the inhibition by ambient nitrate. On the other hand, the more intense and stable atmospheric nitrogen fixation of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 117 publications
1
26
0
Order By: Relevance
“…Nodule number was positively correlated only to variables reflecting either (i) nodule biomass or its biomass proportion within the host plant or (ii) the N nutrition level (plant N concentration or NNI). Novak (2010) has recently suggested that the large increase in nodule number in hypernodulating mutants causes an imbalance between the demand of the nodulated root for carbon and the photosynthetic capacity of the host plant to sustain nodule growth and activity. Likewise, we have previously hypothesised that low nodule SNU of hypernodulating mutants could be accounted for by C competition with excessive nodule growth ).…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Nodule number was positively correlated only to variables reflecting either (i) nodule biomass or its biomass proportion within the host plant or (ii) the N nutrition level (plant N concentration or NNI). Novak (2010) has recently suggested that the large increase in nodule number in hypernodulating mutants causes an imbalance between the demand of the nodulated root for carbon and the photosynthetic capacity of the host plant to sustain nodule growth and activity. Likewise, we have previously hypothesised that low nodule SNU of hypernodulating mutants could be accounted for by C competition with excessive nodule growth ).…”
Section: 2mentioning
confidence: 99%
“…The hypernodulating phenotype was never associated to a substantial increase in N uptake by the mutant plants as compared to their wild type. Instead, hypernodulation most often limited plant growth and productivity (Sagan et al 1993;Bhatia et al 2001;Novak 2010;Voisin et al 2013). Hence, most studies on hypernodulating mutants have reported negative pleiotropic traits related to carbon nutrition such as depressed shoot growth, shortened internodes or fasciation of the stem, and reduction of roots development and growth (e.g., pea : Postma et al 1988;Duc and Messager 1989;Sagan and Duc 1996;Krusell et al 2002;Bourion et al 2007; soybean: Matsunami et al 2004;Voisin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legumes are defined by their unique flower structure, their pod, and the ability of 88% of the species examined so far to form atmospheric N 2 fixing nodules [79,80]. Legumes are only of second importance after grasses to humans, by contributing significantly to grain, pasture and forage, and forestry production [33,81].…”
Section: Nitrogen Fertilization Using Green Manure and Cover Cropsmentioning
confidence: 99%
“…Legumes are known for their symbiotic relationship with Rhizobium s.l. bacteria, enabling them to utilize aerial N 2 , which is inaccessible to many other species (Garg & Geetanjali 2007;Novák 2010). Symbiotic nitrogen fixation makes legumes highly competitive especially in environments limited by mineral (NO − 3 and NH + 4 ) nitrogen and with an adequate phosphorus and potassium supply (Honsová et al 2007;Jackson et al 2008).…”
Section: Introductionmentioning
confidence: 99%